MILITARY AND POLITICAL RIVALRY IN THE CAUCASUS-CASPIAN REGION IN THE 16TH-17TH CENTURIES AND AZERBAIJAN (International journal of artificial intelligence, 2026)
This article explores the growing role of the Caucasus-Caspian region in global geopolitical and geoeconomic processes during the Middle Ages. It provides a detailed examination of the military and political events that took place during this period and reveals the struggle of the main rival forces to establish control over the main trade routes extending from Europe and China, India and Central Asia. In this regard, the extremely important military-strategic and economic significance of one of the main branches of the Great Silk Road is shown - the famous Caspian Route, which ran along the western coast of the Caspian Sea, which became famous back in ancient times. The aim of the study is to analyze the military-political processes occurring in the region during the Middle Ages and to reveal the military events taking place from the 3rd century until the end of the 14th century in the region, which was subjected to spontaneous geo-ethnopolitical pressure from successive diverse military-political forces.In the course of studying this problem, the main responsibilities were to highlight the great migrations of peoples, as well as the invasions of the Arabs, Rus, Seljuks, Mongols, Golden Horde and Timurids, which coincided with the directions of the main world trade routes, including the Caspian, and constituted one of their main strategic goals. In this article, historical-chronological and comparative research methods were used to reveal the problem posed. In the final part of the article, it is noted that the Middle Ages marked the intensification of military and political rivalry in the Caucasus-Caspian region for control over the Caspian route. Beginning in the 10th century, the first signs of a renewed desire of non-Caspian states to penetrate and strengthen their position in this region by one means or another were observed. With the emergence of the powerful Ottoman Empire and strong Azerbaijani states – Ak-Koyunlu - from the mid-15th century, and then from the beginning of the 16th century – The Safavid state, the Caucasus-Caspian region became one of the key elements in the relations between Asia and Europe, which during this period acquired the character of a military-political confrontation.